Peculiarities of the influence of sorbilact and its combination with L-arginine on the level of toxemia and detoxification function of the kidneys in the period of development of endogenous intoxication syndrome - Maksymchuk, N. O.; Konovchuk, V. M. (Journal of Education, Health and Sport, 2019)
Kidney injury in case of endogenous intoxication syndrome of purulent-septic genesis necessitates nephroprotective therapy. The aim of the work was to determine effects of combined use of sorbilact and L-arginine to levels of toxemia and the detoxification function of the kidneys in endogenous intoxication syndrome during the period of it’s development. Methods. Kidneys’ detoxication function have been studied in patients of the following groups. The first group (І, control) consisted of 31 patients with systemic inflammatory response syndrome (SIRS, ICD-10: R-65.2). The second group (ІІ) consisted of 27 patients with endogenous intoxication syndrome who were treated according to Surviving Sepsis Campaign 2016 (standard therapy) [9]. The third group (IІІ) consisited of 29 patients with endogenous intoxication syndrome, who received sorbilact in addition to standard therapy. The fourth group (IV) included 30 patients with endogenous intoxication syndrome who received sorbilact and L-arginine in addition to standard therapy. Sorbilact infusion to patients of III and IV groups was performed at a rate of 6-7 ml/kg body weight, intravenously dripping at a rate of 7-8 ml/min. After the end of infusion of sorbilact, patients of IV group were infused with 4.2% solution of L-arginine (“Tivortin” intravenous drip according to the instructions). Data were obtained and results gathered on the application of drugs in the period of stabilization (according to the state of volumoregulatory and osmoregulatory function) of secondary toxic autoagresion (fourth day of drugs’ application). As a single-celled receptor-effector system, the Paramecium caudatum culture was used. Low Molecular Weight Proteins (LMWP) concentration in blood and urine were determined using a modified method. Results. Development of the syndrome of endogenous intoxication was accompanied by a manifestation of kidney injury. Infusion of sorbilact as a part of complex intensive therapy of endogenous intoxication syndrome has allowed to find out its influence on detoxification functions of the kidneys after a single administration. Under these conditions, sorbilact regulates the ability of the kidneys to excrete toxic substances (р˂0,05). Conclusion. Combination of sorbilact with L-arginine according corresponding indicators of total clearance of toxic substances and Low Molecular Weight Proteins after the first infusion leads to the potentiation of the detoxication effect of sorbilact.